Adenylosuccinate lyase deficiency in a Malaysian patient, with novel adenylosuccinate lyase gene mutations - Chen, B.C.; McGown, I.N.; Thong, M.K.; Pitt, J.; Yunus, Z.M.; Khoo, T.B.; Ngu, L.H.; Duley, J.A. (Kluwer (now part of Springer), 2010)
Most cases of adenylosuccinate lyase (ADSL OMIM 103050) deficiency reported to date are confined to the various European ethnic groups. We report on the first Malaysian case of ADSL deficiency, which appears also to be the first reported Asian case. The case was diagnosed among a cohort of 450 patients with clinical features of psychomotor retardation, global developmental delay, seizures, microcephaly and/or autistic behaviour. The patient presented with frequent convulsions and severe myoclonic jerk within the first few days of life and severe psychomotor retardation. The high performance liquid chromatography (HPLC) profile of the urine revealed the characteristic biochemical markers of succinyladenosine (S-Ado) and succinyl-aminoimidazole carboximide riboside (SAICAr). The urinary S-Ado/SAICAr ratio was found to be 1.02 (type I ADSL deficiency). The patient was compound heterozygous for two novel mutations, c. 445C > G (p. R149G) and c.774_778insG (p.A260GfsX24).